2004
DOI: 10.1007/s00198-004-1652-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of compliance with osteoporosis therapy on fracture rates in actual practice

Abstract: These results indicate that improving compliance in actual practice may significantly decrease osteoporosis-related fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
272
3
9

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 430 publications
(294 citation statements)
references
References 16 publications
10
272
3
9
Order By: Relevance
“…The low adherence levels observed in our study are consistent with rates found in other studies in the literature with shorter follow-up and smaller number patients; Briesacher and colleagues reported a compliance rate of 42% over 1 year of treatment with bisphosphonates, (34) whereas in a different study they reported an MPR 80% of 42.9%, 34.5%, and 30.6% after 1, 2, and 3 years, respectively. (35) Caro and colleagues (30) reported an MPR 80% of 49.4% over a 2-year follow-up; Curtis and colleagues (36) reported 44%, 39%, and 36% at 1, 2, and 3 years, respectively; Penning van Beest and colleagues (37) reported 66%, 58%, 49%, and 40% at 6 months, 1 year, 2 years, and 3 years, respectively; and Siris and colleagues (32) reported 43% over a 2-year follow-up. With regard to persistence, Melo and Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low adherence levels observed in our study are consistent with rates found in other studies in the literature with shorter follow-up and smaller number patients; Briesacher and colleagues reported a compliance rate of 42% over 1 year of treatment with bisphosphonates, (34) whereas in a different study they reported an MPR 80% of 42.9%, 34.5%, and 30.6% after 1, 2, and 3 years, respectively. (35) Caro and colleagues (30) reported an MPR 80% of 49.4% over a 2-year follow-up; Curtis and colleagues (36) reported 44%, 39%, and 36% at 1, 2, and 3 years, respectively; Penning van Beest and colleagues (37) reported 66%, 58%, 49%, and 40% at 6 months, 1 year, 2 years, and 3 years, respectively; and Siris and colleagues (32) reported 43% over a 2-year follow-up. With regard to persistence, Melo and Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence in the literature indicates that adherence to osteoporosis medication is associated with a reduced risk of fractures. (25,30,31) Siris and colleagues reported a linear association between adherence to osteoporosis medications and incidence of fractures during a 2-year treatment period, (32) whereas Curtis and colleagues showed a similar linear effect by evaluating adherence in a time-varying manner over 2.5 years. (33) To date, the studies measuring adherence to OBP treatment and its association with fracture risk have been conducted over short treatment durations, specifically 1 to 3 years.…”
Section: Introductionmentioning
confidence: 98%
“…The effectiveness of a treatment however, depends not only on the efficacy of the used medication but also on persistent drug intake of patients [25][26][27][28]. Drugs do not work in patients who do not take them.…”
Section: The Importance Of Compliance Persistence and Adherence For mentioning
confidence: 99%
“…Different studies in recent years proved significant correlations between compliance and therapeutic results during bisphosphonate therapy [26,34,35]. It was shown that noncompliance with antiresorptive therapies has been associated with a 16-50% increased risk of fracture [26,[34][35][36][37][38].…”
Section: Smaller Increases In Bmd Due To Lower Persistence As a Consementioning
confidence: 99%
See 1 more Smart Citation